If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 + -2x = 0 Reorder the terms: -3 + x + -2x = 0 Combine like terms: x + -2x = -1x -3 + -1x = 0 Solving -3 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 3u+7=-5 | | 0.5(-4+6x)=33.3x+66.6(x+9) | | 15x-5=1+12x | | 25x*76= | | 2-3a=7-2(2a+3) | | 7x+6(-x-17)=-109 | | -8(m-8)=120 | | 7x+.43=y | | -9x+4=-6x+17 | | 12x-8=6x+22 | | 7x-6x-102=109 | | 2x+116-116=180-116 | | 7x-(3x+4)=-2(2x-1)+10 | | 2x^4+x^3-9x^2-4x+4=0 | | 97=4(2+3k)+5 | | 5y-3=8+4(y-2) | | 2(9.2-8)+2(9.2-8)= | | 3d-8=7+8d | | -29=5(2x-1)+2a | | t-12=-4 | | 17-3p=16-4 | | 9x+13-5x=-8x-30+x | | 4(2+3x)=56 | | 2(9.2-8)+2(9.2-8)+9.2= | | 4.05+14.4=4.5(p+3) | | 3(x+65)+3x=2595 | | 8(8-4r)=160 | | 9x+3=4x-9 | | 3r=-11/9 | | 6(5x+6)=30x-3 | | 3x+5=7x+4 | | 10x-2=7x-7.4 |